One‐Pot Multi‐Component Synthesis of Triarylacrylonitriles Directly by Using CaC2 as a Concise Acetylene Source and K4[Fe(CN)6] as an Eco‐Friendly Cyanide Source. Issue 11 (24th March 2018) - Song, Geyang; Li, Zheng
Abstract : An efficient method for the one‐pot multicomponent synthesis of triarylacrylonitriles from various aryl iodides directly by using calcium carbide as a concise acetylene source and potassium hexacyanoferrate(II) as an eco‐friendly cyanide source is described. This protocol benefits from safe, inexpensive and easy‐to‐handle starting materials, good substrate tolerance and simple work‐up procedure. Abstract : An efficient method for the one‐pot multicomponent synthesis of triarylacrylonitriles from various aryl iodides directly by using calcium carbide as a concise acetylene source and potassium hexacyanoferrate(II) as an eco‐friendly cyanide source is described.